Perceptions of selected middle class plantitos/plantitas on benefits of plants in residential interiors during COVID-19 pandemic - Batin, Arra Jane V. (College of Home Economics, University of the Philippines Diliman, 2022)
This study made an attempt to determine the perceptions of selected Filipino middle class plantitos and plantitas on the benefits of the placement of plants in residential interior spaces during COVID-19 pandemic. It examined the spatial considerations of the selected participants with regards to their placement of plants in indoor spaces. It utilized the qualitative descriptive research design, specifically the phenomenological and narrative research approaches. Purposive sampling was used to determine fifteen (15) plantitos and plantitas following the selection criteria of middle-class Filipinos who became plantitos or plantitas during the pandemic and who incorporated plants in their residential interior spaces. The researcher conducted one-on-one online interviews with the respondents as the study’s data gathering method. Treatment of data used thematic and content analysis in order to interpret the advantages of plants based on the participants’ experiences and perceptions. With the application of the Theory of Biophilia in line with Biophilic Design as the framework for data analysis, the results revealed that the practice of placing plants in residential interior spaces was perceived as a way of bringing nature inside, which makes up for the lack of exposure to nature due to the health and safety protocols during the pandemic. The findings suggest that indoor plants provide the following benefits: (1) they elevate the aesthetics, ambiance, and function of interior areas and (2) they contribute to improving the residential space users’ health through their psychological healing effects as well as other sensorial benefits. The study recommends the following spatial considerations as essential in the placement of indoor plants: (1) availability of sunlight and space; (2) aesthetics; and (3) function of space.